Oral leukoplakia; a proposal for simplification and consistency of the clinical classification and terminology - van der Waal, Isaäc (Med Oral Patol Oral Cir Bucal, 2019)
There is a distinct lack of uniformity in the definitions and clinical terminologies related to oral leukoplakia and leukoplakialike lesions and disorders. Proposals have been put forward to subclassify leukoplakia into a homogeneous and a non-homogeneous type based on color only, being either predominantly white or mixed white-and-red, respectively, irrespective of the texture of the lesion. In this proposal there is no need anymore to regard the poorly defined proliferative verrucous leukoplakia as a separate entity. Since keratosis is primarily a histopathological term, its clinical use is discouraged. Alternative terminology for these so-called keratotic lesions and disorders has been put forward. Finally, a suggestion has been made to rename the term hairy leukoplakia, being a well defined, not potentially malignant disorder particularly related to HIV-infection, into 'EBV-positive white lesion of the tongue' (EBVposWLT). Key words:Potentially malignant oral disorders, oral leukoplakia, oral keratosis, hairy leukoplakia.